Penggunaan Sonkeigo Dan Kenjougo Dalam Drama Ouroboros: Kono Ai Koso Seigi - Fadhilatul Annisa; Maulluddul Haq (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Sonkeigo and kenjougo are types of respectful language (keigo). This study aimed at describing the various forms of sonkeigo and kenjougo in Drama Ouroboros: Kono Ai Koso Seigi. Indicators of the types sonkeigo and kenjougo is based on the theory of Sudjianto and Dahidi. This study was a qualitative research with uses a qualitative descriptive approach. The data in this study using sentences that containing sonkeigo and kenjougo and the data source was a drama Ouroboros: Kono Ai Koso, Seigi. Data collection using the method of simak bebas libat cakap (SBLC) and notes. In data analysis using the Miles and Huberman models; data reduction, data display, and verification/conclusions. The result of this study were; 54 words of sonkeigo and 47 words of kenjougo.